Incidence of anemia and red blood cell (RBC) transfusion requirement in breast cancer - Nur Aklina Ramli; Salfarina Iberahim Sal Salfarina; Hasmah Hussin; Ahmad Arif Che Ismail (Babol University of Medical Sciences, 2023)
Background: Cancer-related anaemia is one of the main burdens in oncology, although the available data on its prevalence and treatment options such as blood transfusion are often contradictory. This study aimed to evaluate the prevalence of anaemia and the requirement for packed red blood cell (PRBC) transfusion among women with breast cancer (BC) and to determine the associated factors for chemotherapy-induced anaemia (CIA). Methods: This cross-sectional retrospective study conducted in Kelantan involved 104 newly diagnosed female BC patients from 2015 to 2016 who underwent chemotherapy. For statistical analysis, chi-square was used to compare between CIA and non-CIA groups. In addition, simple and multiple logistic regression were used to determine the association of the CIA. Results: Our study revealed that 34.6% (n=36) of patients had mild anaemia, and 59.6% (n=62) had normal haemoglobin at pre-chemotherapy. The prevalence of anaemia increased from 40.4% to 77% at the end of our study. About 30.8% of patients received PRBC transfusion during chemotherapy with mean haemoglobin before the first transfusion of 7.9 g/dl. CIA was observed in 54.8% of cases. There was no significant association between CIA concerning the patient characteristic, cancer characteristic, or cancer treatment. Conclusion: We concluded that a significant proportion (40.4%) of BC patients was anaemic even before chemotherapy, with the red blood cell requirements up to 30.8% throughout chemotherapy. A larger prospective study is needed to determine the predictors for the CIA and subsequently improve patient management.